The terror part of terrorism. - Hudnall Stamm, B. (IEEE Engineering in medicine and biology magazine)
As human beings, we share the trait of being able to experience extreme fear A variety of events can bring about this level of distress, some of which occur naturally and others that are caused by human action. One such event, terrorism, results from human action. In recent times, there has been a shift from conventional weapons for war and terrorism to a type of weapon of mass destruction (WMD) that includes chemical, biological, radiological, nuclear, and high yield explosives (CBRNE) weapons These types of weapons, in addition to their obvious effects, may be particularly capable of causing widespread fear, confusion, and stress that may alter the long-term health of affected communities and the larger community's sense of well-being.